Testing a model of Islamic corporate financial reports: some experimental evidence - Sulaiman, Maliah (KENMS-IIUM Press, 2001)
Given the fact that religion stands at the core of some cultures, and that Islam is a significant force influencing the manner in which Muslims conduct their public and private lives, the influence of Islam on accounting may be significant. In line with this, Baydoun and Willett (1994 and 2000) suggested that the current value balance sheet and the value added statement would meet Islam’s objectives of socio-economic justice and accountability, thus satisfying the needs of Muslim users to a greater extent than would the traditional historical cost balance sheet and the profit and loss statement. Baydoun and Willett’s model of Islamic corporate financial reports was initially tested through a questionnaire survey by Sulaiman (1998) which, surprisingly, found no differences in the perceptions of usefulness between Muslim and non- Muslim respondents. Before dismissing such an important conceptual model for lack of empirical support, an alternative empirical test should be conducted in which greater control for internal validity of data is achieved. To this end, the researcher examined the same issue using a laboratory experiment. The results of the experiment proved to be consistent with Sulaiman (1998). No significant differences in the perception of usefulness of the current value balance sheet and the value-added statement between Muslim and non-Muslim